The value of and demand for diverse news sources - Evan M. Calford; Anujit Chakraborty (University of California, Department of Economics, 2023)
We study the value of and the demand for instrumentally-valuable information in a simple decision environment where signals are transparently polarized. We find that in both information aggregation and acquisition, subjects use sophisticated heuristics to counter the polarization in signals. Even though the number of precise Bayesian reports are small, most subjects (64%) generate unpolarized reports even when faced with polarized signals. Subjects placed in a market place of information rarely end up buying polarized signals and instead overwhelmingly opt for diverse information. The demand for diverse information increases as diverse information becomes more valuable and decreases as it becomes more expensive.
Keywords: D90; D91; D81; 330; Experimental economics; information acquisition; information aggregation